Rethinking Social Action Through Music : The Search for Coexistence and Citizenship in Medellín's Music Schools. - Baker, Geoffrey. (Open Book Publishers, 2021)
How can we better understand the past, present and future of Social Action through Music (SATM)?This ground-breaking book examines the development of the Red de Escuelas de Música de Medellín (the Network of Music Schools of Medellín), a network of 27 schools founded in Colombia's second city in 1996 as a response to its reputation as the most dangerous city on Earth.